Cultural Creativity and Transnational Belonging: A Glimpse on Transnational Research in Ethiopia and Beyond (Aethiopica, 2019)
The three books under review provide different approaches to North-East African transnational studies. However, their descriptions of migration and transnational life are unified in that they focus on the migrants not as mere victims of their plight but on their agency and creativity both during the process of migration and in the descriptions of their settling and making a new life.
Keywords: diaspora studies; ethnic identification; Nuer; ethnography; transnationalism